Developing an architecture model for enterprise knowledge - Jafari, Mostafa; Akhavan, Peyman; Nouranipour, Elham (Management decision, 2009)
Purpose - The main objective of this paper is to explore the role of knowledge architecture in an enterprise and to provide a model to architect enterprise knowledge based on the Zachman framework.Design methodology approach - This is a conceptual article providing a knowledge architecture model for an organization based on the Zachman framework that discussed several perspectives from the knowledge management point of view and information technology. To confirm the validity of the model a questionnaire was designed, applied and then analyzed by some statistical methods.Findings - The paper provides a conceptual knowledge architecture model that can be applied to Iranian organizations practically. The validity of this model is confirmed by polling the opinion of knowledge architecture experts.Research limitations implications - The lack of resources directly related to the subject of the research, the novelty of this kind of research in Iran and the lack of organizations which perform a knowledge architecture model in reality are the restrictions of this research. The authors' suggestion for further research studies is to execute the model and survey from foreigner experts.Practical implications - The paper may be beneficial for enterprise architects in the knowledge area.Originality value - The paper may be of high value to researchers in the knowledge management field and to practitioners involved with KM adoption in the organizations. It gives valuable information and guidelines that hopefully will help the leaders and the senior knowledge management managers to accomplish KM through their organization successfully.